Perceptions on online intervention for overweight/obese adolescents: a preliminary study - Félix, Sílvia (2020)
Satisfaction perception of participants with regard to APOLO-teens and associated behavior and psychological factors are investigated. APOLO-teens is a psycho-educational program implemented by Facebook®, during six months, supplementary to conventional hospital treatment for obese/overweight adolescents. Fifty-two adolescents (71.2% females; M = 14.98 years, DP = 1.63) participated and evaluated by self-reported measures with regard to depression symptoms, life quality and feeding behavior at the start, in the middle (three months) and at the end (six months) of the intervention. A questionnaire was filled with their perceptions on the intervention program after 6 months. As a rule, positive perceptions were given. Chat sessions had low adhesion and post participants preferred a shorter intervention. Preferred theme comprised physical activity, whilst the less appreciated theme was health food. There was a negative co-relationship between satisfaction with results and depression and dysfunctional food behavior. It is important (1) to reconsider duration and make chat and health food more attractive; (2) give priority to depression symptoms and dysfunctional food behavior for better adhesion to intervention.